Design of fluorinated hyperbranched polyether copolymers for 19F MRI nanotheranostics. Issue 24 (11th May 2020) - Celentano, Wanda; Neri, Giulia; Distante, Francesco; Li, Min; Messa, Piergiorgio; Chirizzi, Cristina; Chaabane, Linda; De Campo, Floryan; Metrangolo, Pierangelo; Baldelli Bombelli, Francesca; Cellesi, Francesco
Abstract : 19 F MRI contrast agents and drug nanocarriers based on fluorinated hyperbranched polyether copolymers. Abstract : Fluorinated hyperbranched polyether copolymers of tuneable composition and architecture were designed and synthesized to develop drug nanocarriers as well as 19 F MRI contrast agents. The performance of these nanomaterials in terms of nanoparticle formation and drug (dexamethasone) loading, as well as 19 F-MRI detectability, was evaluated. These polymers were obtained through controlled ring opening multibranching polymerisation, and the presence of pendant fluorinated groups was obtained by copolymerisation of glycidol and the fluorinated glycidyl ether 2-[(2, 2, 2-trifluoroethoxy)methyl]oxirane. By varying polymer composition and architecture during the synthesis, we controlled the key properties of the nanomaterials, including the fluorine content, drug loading, nanoparticle size, and MRI signal. The macromolecules were cytocompatible, with the ability to deliver dexamethasone on damaged kidney glomerular cells in vitro ; therefore they hold promise as new generation 19 F MRI nanotheranostics.